PENERAPAN PRINSIP GOOD CORPORATE GOVERNANCE PADA PERUSAHAAN PENJAMINAN (STUDI KASUS PT JAMKRINDO) - MUHAMMAD MUCHLAS ROWI (Institut Bisnis Muhammadiyah Bekasi, 2020)
The application of the principles of Good Corporate Governance was suppressed after economic crises in various countries in the 1990s. When observing the major financial scandals that were exposed, the public began to question the performance of the big companies involved in this scandal which went against the principles of Good Corporate Governance regarding accountability, equity, integrity, transparancy and responsibility. PT Jamkrindo is a state-owned company engaged in underwriting with program and nonprogram products. PT Jamkrindo is here to participate in elevating MSME-K actors to become more independent, develop and advance. PT Jamkrindo must implement good governance or Good Corporate Governance. This is important because so far MSMEs are not considered to need good corporate governance. Even though MSMEs contribute greatly to the Indonesian economy